The end of the world is just the beginning : mapping the collapse of globalization - Zeihan, Peter (New York Harper Business, 2022)
As isolationism and realism become the dominant values of a previously interconnected world, the logic that motivated international relations and global trade must be reevaluated. Zeihan uses a mixture of geographical knowledge, political history, and sharp analysis to predict the shape of the next twenty years on the world stage"
Includes bibliographical references and index.
Keywords: Economic development--Forecasting. International relations--Forecasting. Geopolitics